2009
DOI: 10.1371/journal.pbio.1000256
|View full text |Cite
|
Sign up to set email alerts
|

ZBED6, a Novel Transcription Factor Derived from a Domesticated DNA Transposon Regulates IGF2 Expression and Muscle Growth

Abstract: This study identifies a previously uncharacterized protein, encoded by a domesticated DNA transposon, called ZBED6 that regulates the expression of the insulin-like growth factor 2 (IGF2) gene, and possibly numerous others, in all placental mammals including human.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
206
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 153 publications
(220 citation statements)
references
References 26 publications
14
206
0
Order By: Relevance
“…Z inc finger BED domain-containing protein 6 (ZBED6) is a recently discovered transcription factor restricted to and highly conserved among placental mammals (1). The intron-less ZBED6 has evolved from a domesticated DNA transposon and is located in one of the first introns of another gene, zinc finger CCCH-type containing 11A (ZC3H11A), with which it has no sequence homology.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Z inc finger BED domain-containing protein 6 (ZBED6) is a recently discovered transcription factor restricted to and highly conserved among placental mammals (1). The intron-less ZBED6 has evolved from a domesticated DNA transposon and is located in one of the first introns of another gene, zinc finger CCCH-type containing 11A (ZC3H11A), with which it has no sequence homology.…”
mentioning
confidence: 99%
“…ZBED6 belongs to the CCCH zinc-finger BEAT and DREF (BED) domain-containing family and contains two DNA-binding BED domains and one hobo-Ac-Tam3 (hATC) dimerization domain. ZBED6 has a broad tissue distribution in mammals (1). In muscle tissue of pigs, it has been observed that ZBED6 negatively regulates insulin-like growth factor-2 (IGF2) transcription (1).…”
mentioning
confidence: 99%
See 3 more Smart Citations